2021
DOI: 10.1177/15500594211054297
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamic Brain Connectivity in Individuals With Sickle Cell Disease and Chronic Pain Secondary to Hip Osteonecrosis

Abstract: Individuals with sickle cell disease (SCD) exhibit changes in static brain connectivity in rest. However, little known as chronic pain associated with hip osteonecrosis affects dynamic brain connectivity during rest and the motor imagery task. The aim of this study was to investigate the characteristics of the dynamic functional brain connectivity of individuals with SCD and chronic pain secondary to hip osteonecrosis. This is a cross-sectional study comparing the dynamic brain connectivity of healthy individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“… 102 Another cross-sectional study observed a lower “full synchronization time” (described as the time required for a network to become approximately complete) in sickle cell patients with chronic hip pain. 95 In a longitudinal study examining changes in brain activity following multimodal pain therapy, a correlation between pain decrease and theta global efficiency increase was observed. 37 A longitudinal neurofeedback study found negative correlations of changes in pain with fractional occupancy, mean dwell times, and transition probability from low to high alpha state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 102 Another cross-sectional study observed a lower “full synchronization time” (described as the time required for a network to become approximately complete) in sickle cell patients with chronic hip pain. 95 In a longitudinal study examining changes in brain activity following multimodal pain therapy, a correlation between pain decrease and theta global efficiency increase was observed. 37 A longitudinal neurofeedback study found negative correlations of changes in pain with fractional occupancy, mean dwell times, and transition probability from low to high alpha state.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 76 studies were included. 1 , 5 8 , 10 , 11 , 15 , 16 , 18 27 , 30 33 , 35 , 37 49 , 51 , 56 , 59 , 60 , 63 , 66 69 , 74 76 , 79 , 80 , 82 , 89 91 , 95 98 , 100 105 , 109 , 110 , 112 115 , 120 , 122 , 124 126 Figure 1 depicts the PRISMA flow diagram of study selection along with reasons for study exclusion at every stage.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, it allows us to track the trajectory of pain development after applying certain therapies. This stratification of patients could serve to guide and inform future treatment and adds an additional quantitative objective measure of pain (Thibaut et al, 2017;Ahn et al, 2019;Yüksel et al, 2019;Santana et al, 2021;.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%
“…More importantly, it allows us to track the trajectory of pain development after applying certain therapies. This stratification of patients could serve to guide and inform future treatment and adds an additional quantitative objective measure of pain ( Thibaut et al, 2017 ; Ahn et al, 2019 ; Yüksel et al, 2019 ; Santana et al, 2021 ; Heitmann et al, 2022 ).…”
Section: Types Of Potential Eeg Biomarkers and Their Utility In Chron...mentioning
confidence: 99%